Therapeutic potential of adipose derived stromal cells for major skin inflammatory diseases - Galera, Marina Ramírez; Svalgaard, Jesper; Woetmann, Anders (Frontiers in Medicine, 2024)
Inflammatory skin diseases like psoriasis and atopic dermatitis are chronic inflammatory skin conditions continuously under investigation due to increased prevalence and lack of cure.Moreover, long-term treatments available are often associated with adverse effects and drug resistance. Consequently, there is a clear unmet need for new therapeutic approaches. One promising and cutting-edge treatment option is the use of adipose-derived mesenchymal stromal cells (AD-MSCs) due to its immunomodulatory and anti-inflammatory properties.Therefore, this mini review aims to highlight why adipose-derived mesenchymal stromal cells are a potential new treatment for these diseases by summarising the pre-clinical and clinical studies investigated up to date and addressing current limitations and unresolved clinical questions from a dermatological and immunomodulatory point of view.